Delineation of the structure-function relationships within the fourth intracellular loop of dopamine D1-like receptors - Zhang, Dongling (University of Ottawa (Canada), 2004)
The present study focuses the attention on a region of CT known to participate in the formation of a fourth intracellular loop (IL.4). The central objective of this study is to investigate the potential role of variant residues within IL4 region in regulating distinct D1-like functional properties. Results obtained from ligand binding and agonist-dependent G protein coupling studies using chimeric receptors reveal a crucial role of the N-terminal segment of IL4 (IL4N) in regulating receptor expression, ligand binding and dopamine (DA) potency of D1-like subtypes. Moreover, results show that the C-terminal segment of IL4 (IL4C) regulate the extent of IL4N-mediated effects on DA binding and potency mostly through interfering intramolecular interactions. Meanwhile, agonist-independent G protein coupling data suggest that the Dl-like subtype-specific agonistindependent activity relies exclusively on intramolecular interactions regulated by IL4N segment. Taken together, the present study underscores the important roles of IL4N and IL4C segments of D1-like receptors in regulating their distinct ligand binding and G protein coupling properties, a finding that may prove beneficial for the development of D1A/D1 and D1B/D5 subtype-specific ligands. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.; Biology, Cell.